CaMKII activity is reduced in skeletal muscle during sepsis. Issue 6 (16th April 2013) - Aversa, Zaira; Alamdari, Nima; Castillero, Estibaliz; Muscaritoli, Maurizio; Fanelli, Filippo Rossi; Hasselgren, Per‐Olof
Abstract Exercise‐induced muscle hypertrophy is associated with increased calcium/calmodulin‐dependent protein kinase II (CaMKII) expression and activity. In contrast, the influence of muscle atrophy‐related conditions on CaMKII is poorly understood. Here, we tested the hypothesis that sepsis‐induced muscle wasting is associated with reduced CaMKII expression and activity. Sepsis, induced by cecal ligation and puncture in rats, and treatment of rats with TNFα, resulted in reduced total CaMKII activity in skeletal muscle whereas autonomous CaMKII activity was unaffected. The expression of CaMKIIδ, but not β and γ, was reduced in septic muscle. In additional experiments, treatment of cultured myotubes with TNFα resulted in reduced total CaMKII activity and decreased levels of phosphorylated glycogen synthase kinase (GSK)‐3β, a downstream target of CaMKII. The present results suggest that sepsis‐induced muscle wasting is associated with reduced CaMKII activity and that TNFα may be involved in the regulation of CaMKII activity in skeletal muscle. Decreased phosphorylation (consistent with activation) of GSK‐3β may be a consequence of reduced CaMKII activity, indicating that inhibited CaMKII activity may be involved in the catabolic response to sepsis. J. Cell. Biochem. 114: 1294–1305, 2013. © 2012 Wiley Periodicals, Inc.